Development of Learning Devices Based on Ethnoscience Project Based Learning to Improve Students’ Critical Thinking Skills - Luthfia Hanum*; Muhammad Hasan; Andi Ulfa Tenri Pada; Hafnati Rahmatan; Ratu Fazlia Inda Rahmayani; Elisa Elisa; Yusrizal Yusrizal (Universitas Syiah Kuala, 2023)
One of the causes of the low critical thinking skills of participants is caused by the learning process that focuses on mastering concepts alone without involving students to construct knowledge independently. Less comprehensive learning tools are the main obstacles that are often encountered in the implementation of learning. Project based learning is a constructivist method that is able to involve students to construct knowledge empirically, one of which is by utilizing the content of ethnoscience as a contextual approach in project learning. This study aims to develop a quality ethnoscience-based Project based learning devices in terms of content validity and empirical validity. This study uses the research and development method with the ADDIE model. The research was conducted at SMA Negeri 1 Gandapura. The research instrument used a validation sheet, student response questionnaires and teacher response questionnaires. Data analysis used the Aiken V coefficient for critical thinking skills test questions; Interclass correlation coefficient for lesson plans, Student Worksheets and Handouts; percentage formula for teacher and student response questionnaires. The results showed that the ethnoscience-based Project based learning devices were categorized as very feasible and could improve the critical thinking skills of students with an N-gain of 0.88 which was classified as high, and received a positive response from the teacher with a percentage of 96.71% and students by 86.35%